Synthesis, characterization and thermal properties of nanoencapsulated phase change materials via sol-gel method - Tahan Latibari S.; Mehrali M.; Mehrali M.; Indra Mahlia T.M.; Cornelis Metselaar H.S. (Elsevier Ltd, 2023)
This study focuses on preparing PCM (phase change material) nanocapsules which contain PA (palmitic acid) as core and SiO2 as shell materials. For the first time encapsulation of phase change materials is synthesized in nano scale via the sol-gel method by changing the value of pH in the range of 11-12. The morphology and the mean size of three samples are compared and the influences of different pH values on the particle size studied. This investigation reveals that the encapsulation ratio of PA is increased from 83.25 to 89.55 percent by increasing the pH value in the range of 11-12. The nanoencapsulated PCMs are arranged uniformly and spherically with mean diameter sizes 183.7, 466.4 and 722.5nm for pH values of 11, 11.5 and 12, respectively. A thermal cycling test is done by 2500 melting/freezing cycles to determine thermal reliability and chemical stability of the nanoencapsulated PCMs. The thermal conductivity of the encapsulated PA is significantly improved compared to pure PA. As a result, the prepared PA/SiO2 nanocapsules are appropriate PCMs for slurry thermal energy storage applications because of their acceptable thermal properties, good thermal reliability, chemical stability, uniform morphology and thermal conductivities. 2013 Elsevier Ltd.